2022
DOI: 10.1111/aec.13160
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in the threatened soft coral Dendronephthya australis in temperate eastern Australia

Abstract: The endangered soft coral Dendronephthya australis faces substantial population decreases in central eastern Australian waters. Despite uncertainty about the cause of these declines, the population genetics of the species has not been investigated. Genetic analysis suggests that D. australis is a single species within the family Nephtheidae, confirming identifications based on morphological characteristics only. Soft coral colonies were distributed from Seahorse Gardens in Port Stephens to Jervis Bay in temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Without these clusters of colonies, their ability to reproduce may be hindered. Although there is evidence that D. australis can asexually propagate (Larkin et al 2023b), genetic analyses indicate that sexual reproduction is likely its primary mode of proliferation (Williamson et al 2022), as has been found for other Malacalcyonacean species (McFadden 1997;Bastidas et al 2001). A recent study provides evidence that D. australis is a gonochoric broadcast spawner (Larkin et al 2023b).…”
Section: Discussionmentioning
confidence: 98%
“…Without these clusters of colonies, their ability to reproduce may be hindered. Although there is evidence that D. australis can asexually propagate (Larkin et al 2023b), genetic analyses indicate that sexual reproduction is likely its primary mode of proliferation (Williamson et al 2022), as has been found for other Malacalcyonacean species (McFadden 1997;Bastidas et al 2001). A recent study provides evidence that D. australis is a gonochoric broadcast spawner (Larkin et al 2023b).…”
Section: Discussionmentioning
confidence: 98%
“…For species identification, three genetic markers were PCR-amplified. The mitochondrial marker ribosomal 16S gene was amplified using primers DN1-F (5′-AGGCTACTTAAGTATAGGGG-3’) and DN1-R (5′-AACTCTCCGACAATATTACGC-3′), with PCR conditions as described in [ 43 ]. The second markers were the oxidase subunits I and II (cox1 and 2), which were generated based on the available sequences of Dendronephthya hemprichi (native to the Red Sea) in NCBI at the time (GU355996.1): DhCox12F AGAGTGTTCTCACCTACTTTAG and DhCox12R GTTTAGCAGAAAATGTGGGTAT.…”
Section: Methodsmentioning
confidence: 99%
“…To date, species classification of the family Nephtheidae has mainly been based on morphology [ 42 ]. Recent phylogenetic analysis using a whole mitochondrial genome provides better resolution of the topology of this family [ 43 , 44 ]. However, further genetic information is required in order to resolve species-level phylogeny amongst genera in this family [ 42 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…For species identification, two genetic markers were PCR-amplified. The mitochondrial marker ribosomal 16S gene was amplified using primers DN1-F (5'-AGGCTACTTAAGTATAGGGG-3') and DN1-R (5'-AACTCTCCGACAATATTACGC-3'), with PCR conditions described in (Williamson et al, 2022). The second marker was the oxidase subunit II and I (cox1 and 2) which were generated based on the available sequences of Dendronephthya hemprichi (native to the Red Sea) in NCBI at the time (GU355996.1), DhCox12F AGAGTGTTCTCACCTACTTTAG, DhCox12R GTTTAGCAGAAAATGTGGGTAT.…”
Section: Dna Extractionmentioning
confidence: 99%